2019
DOI: 10.31744/einstein_journal/2020gs4442
|View full text |Cite
|
Sign up to set email alerts
|

Legal demands of the tiotropium bromide for treatment of chronic obstructive pulmonary disease and their financial impact for the State of Paraná, Brazil

Abstract: Objective To analyze the legal demands of tiotropium bromide to treat chronic obstructive pulmonary disease.Methods We included secondary data from the pharmaceutical care management systems made available by the Paraná State Drug Center.Results Public interest civil action and ordinary procedures, among others, were the most common used by the patients to obtain the medicine. Two Health Centers in Paraná (Londrina and Umuarama) concentrated more than 50% of the actions. The most common specialty of physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
5
0
6
Order By: Relevance
“…8 Tal fato é destacado pelo exemplo exposto no estudo de Silva et al (2017), 9 em que a incorporação da alfaglicosidase ao SUS em 2014 gerou queda nos gastos com a judicialização deste: de R$ 2.153.732,50 em 2015 para R$ 637.198,97 de janeiro a agosto de 2016. Dada a importância disso, oito estudos 9,10,14,15,23,24,25,28 discorreram sobre os custos de medicamentos e seu impacto financeiro, além de 12 publicações 3,8,9,10,16,19,21,[23][24][25][26][27] dissertarem sobre a demanda de medicamentos.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…8 Tal fato é destacado pelo exemplo exposto no estudo de Silva et al (2017), 9 em que a incorporação da alfaglicosidase ao SUS em 2014 gerou queda nos gastos com a judicialização deste: de R$ 2.153.732,50 em 2015 para R$ 637.198,97 de janeiro a agosto de 2016. Dada a importância disso, oito estudos 9,10,14,15,23,24,25,28 discorreram sobre os custos de medicamentos e seu impacto financeiro, além de 12 publicações 3,8,9,10,16,19,21,[23][24][25][26][27] dissertarem sobre a demanda de medicamentos.…”
Section: Discussionunclassified
“…13,21 No que tange aos medicamentos, o número de medicamentos demandados foram descritos em 14 publicações. 3,[8][9][10][11][12]16,19,21,[23][24][25][26][27] Já a somatória dos custos também foram descritas. 9,10,14,15,23,24,25,28 Dados referentes a incorporação dos medicamentos em listas oficiais encontram-se em 9 estudos.…”
Section: Conclusãounclassified
See 2 more Smart Citations
“…Dear Editor, Szpak et al, demonstrated an expressive increase in expenses by the State Health Authority of Paraná associated to judicialization of access to tiotropium bromide for treatment of chronic obstructive pulmonary disease (COPD), and the relevant individual financial impact provided by the drug. (1) Based on these findings, the authors indicated the need to revise the clinical protocol of the disease, and insert new therapeutic options on the National Formulary of Essential Medicines. However, although we agree with this observation, we understand the rationale presented by the authors lacks more consistent evidence to guide the process of adding technologies to the Brazilian Public Health System (SUS -Sistema Único de Saúde).…”
Section: Doi: 1031744/einstein_journal/2020ce5754mentioning
confidence: 99%